Acute gastroenteritis—changes to the recommended original oral rehydrating salts: a review - Lifschitz, Carlos; Kozhevnikov, Oleksii; Oesterling, Christine; Anbar, Amira; Walker, Steven (Frontiers in Pediatrics, 2023)
The World Health Organization recommended a formulation of oral rehydration salts as the intervention of choice for the treatment of acute gastroenteritis. While of value for the replacement of fluids and electrolytes, the formulation does not reduce stool volume, frequency, or symptom duration. This may prevent wide acceptance. To increase tolerability, shorten the duration of diarrhea and improve parental quality of life, several modifications to the original formula have been proposed. These include; low osmolarity, rice-based, glucose polymers as an alternative to glucose, the addition of probiotics, prebiotics and/or zinc, and various other ingredients. Here we summarize evidence regarding such changes and additions.